Application of computer imaging, stripping voltammetry and mass spectrometry to study the effect of lead (Pb-EDTA) on the growth and viability of early somatic embryos of Norway spruce (Picea abies /L./ Karst.) - Petrek, Jirí; Vítecek, Jan; Vlasínová, Helena; Kizek, René; Kramer, Karl J; Adam, Vojtech; Klejdus, Borivoj; Havel, Ladislav (Analytical and bioanalytical chemistry, 2005)
Image analysis (IA) was used to determine the areas and circumferences of clusters of early somatic embryos (ESEs) of the Norway spruce (Picea abies /L./Karst.). Results obtained from IA were compared with the fresh weights of the ESE clusters and their esterase activities. The areas of the ESE clusters correlated well with both the increases in fresh weight (R2=0.99) of the ESEs and their esterase activities (R2=0.99). In addition, we studied the viability of the ESEs, which was determined by (a) double staining with fluorescein diacetate and propidium iodide (the resulting fluorescence was quantified by IA) and (b) determining esterase activity using a spectrofluorimetric detector. The results obtained with IA and esterase assay were comparable (the deviation between the tangents of the bisectors was 6.4%). IA was also used to study the effect of Pb-EDTA chelate (50, 250 and 500 microM) on the viability of the ESEs and on the growth of clusters. The presence of Pb-EDTA markedly slowed the growth of ESEs clusters (by more than 65% with 250 microM of Pb-EDTA after 288 h of cultivation) and decreased the viability of ESEs (by more than 30% with 500 microM of Pb-EDTA after 288 h of cultivation). The lead concentration in the ESEs was determined by differential pulse anodic stripping voltammetry and increased with the external lead concentration and the time of treatment from 100 to 600 pg Pb/100 mg of fresh weight of ESEs. Glutathione is a diagnostic marker of the influence of Pb-EDTA on ESEs and its content was determined by high-performance liquid chromatography coupled with mass spectrometry. The glutathione content changed linearly with treatment time and the applied external lead concentration. The highest glutathione content was obtained at 250 microM of Pb-EDTA after 192 h of cultivation.
Keywords: Image Processing, Computer-Assisted; hmotnostní spektrometrie; Edetic Acid; smrk; Lead; Mass Spectrometry; EDTA; potenciometrie; Potentiometry; počítačové zpracování obrazu; olovo; semena rostlinná; Seeds; Picea